SUSTAINABILITY IN A GREEN ECONOMY: A LITERATURE REVIEW OF STRATEGIES AND IMPLEMENTATION - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The green economy aims to harmonise economic growth with environmental protection, by adopting environmentally friendly and sustainable approaches. The study found that key strategies that support a green economy include the use of renewable energy, improved energy efficiency, better waste management and sustainable agricultural practices. In addition, government regulatory support and incentives, as well as the role of technology and innovation, are critical in overcoming implementation challenges. While green economy implementation faces barriers such as high initial costs and resistance from some stakeholders, the long-term benefits are far more significant. These benefits include job creation, improved quality of life, and climate change mitigation. Therefore, deep collaboration between the government, private sector and communities is required to achieve comprehensive sustainability. The research concludes that with an integrated and participatory approach, the transition to a green economy can be successfully realised, making sustainable development the foundation of future economic growth.